Strengthening Muslim family institution: a management perspective - Islam, Muhammad Khairul; Islam, Rafikul (UPM Press, 2011)
Today, the Muslim society is embroiled with many problems and there are reasons for this. It is the view of many Muslim scholars that presently the Muslim family institution is not as strong as it is supposed to be. The objective of the present research was to apply Quality Function Deployment (QFD) and Analytic Hierarchy Process (AHP) to strengthen Muslim family institution. According to the QFD framework, two types of information are required, namely the ‘what’ and ‘how’. The ‘what’ includes the requirements for having a strong Muslim family institution, while the ‘how’ involves the ways to fulfil those equirements. Data are collected from 40 Muslim scholars on a personal contact basis. AHP has been applied to prioritize the requirements (‘what’). The QFD exercise provides the prioritized ‘technical’ requirements (‘how’). The findings are expected to provide guidelines for having a strong family institution that can contribute towards developing a healthy society.